Design of an Instructional Video on Molecular Gastronomy for Vocational High School Students - Vera Santika; Siti Fathonah (Universitas Negeri Padang, 2026)
Molecular gastronomy learning in vocational culinary education requires instructional media that can visually demonstrate processing techniques and procedures, enabling students to better understand complex concepts. However, learning resources specifically addressing molecular gastronomy remain limited. This study aimed to develop an instructional video on molecular gastronomy applied to cendol processing and to evaluate its material quality, media quality, and student responses. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the Analysis, Design, and Development phases. The participants consisted of three material experts, three media experts, and 27 students from SMK Negeri 6 Semarang. Data were collected through material validation sheets, media validation sheets, and student response questionnaires using a Likert scale. Quantitative descriptive analysis was conducted based on mean scores. The results indicated that the instructional video obtained a mean score of 4.52 from material experts and 4.48 from media experts. Student responses yielded a mean score of 4.57. All scores fell within the 4.20–5.00 interval, indicating very high feasibility and attractiveness. These findings suggest that the developed instructional video is suitable for supporting molecular gastronomy instruction in vocational high schools. Nevertheless, the effectiveness of the media in improving student learning outcomes was not examined in this study.